Pengembangan Aplikasi Manajemen Event Pada Komunitas Bonsai Indonesia Berbasis Web - Chasan Ali Mujahid; Nurudin Santoso; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Bonsai is a work of art that is quite popular among the people. Domestically, the art of bonsai continues to grow, marked by the continued increase in branches of the Indonesian Bonsai Fan Association (PPBI) community. As the development of bonsai art is increasingly in demand, it is not surprising that in Indonesia there are often exhibition events held. Based on these problems the background of the bonsai community to develop a web-based bonsai community event management application as a means to facilitate the lovers of bonsai art in participating and organizing exhibition events or bonsai competitions at local and national levels. In this study, researchers built a website-based application that functions to create events, register at an event and manage the event management. In the system requirements analysis phase, 20 functional requirements and 1 non-functional requirements are obtained. In conducting research, the development method used is Rapid Application Development (RAD) and is implemented using the laravel framework which is a framework for building a website with the Model View Controller concept. After implementation, the system is then tested using unit testing, validation testing, and usability testing. Unit testing is performed on 3 main functions of the system and is 100% valid. Validation testing is performed on all system functions and produces 100% valid. In addition, a usability test is performed to test the user's ease of operation of the system. The results of the usability test were obtained from respondents using the SUS method resulting in a Likert value of 83.5 from user respondents and a Likert value of 81.5 from the organizing respondents.